Daratumumab, lenalidomide, and dexamethasone versus lenalidomide and dexamethasone alone in newly diagnosed multiple myeloma (MAIA): overall survival results from a randomised, open-label, phase 3 trial. Issue 11 (November 2021) - Facon, Thierry; Kumar, Shaji K; Plesner, Torben; Orlowski, Robert Z; Moreau, Philippe; Bahlis, Nizar; Basu, Supratik; Nahi, Hareth; Hulin, Cyrille; Quach, Hang; Goldschmidt, Hartmut; O'Dwyer, Michael; et al.
Summary: Background: In the primary analysis of the phase 3 MAIA trial (median follow-up 28·0 months), a significant improvement in progression-free survival was observed with daratumumab plus lenalidomide and dexamethasone versus lenalidomide and dexamethasone alone in transplantation-ineligible patients with newly diagnosed multiple myeloma. Here, we report the updated efficacy and safety results from a prespecified interim analysis for overall survival. Methods: MAIA is an ongoing, multicentre, randomised, open-label, phase 3 trial that enrolled patients at 176 hospitals in 14 countries across North America, Europe, the Middle East, and the Asia-Pacific region. Eligible patients were aged 18 years or older, had newly diagnosed multiple myeloma, had an Eastern Cooperative Oncology Group performance status score of 0–2, and were ineligible for high-dose chemotherapy with autologous stem-cell transplantation because of their age (≥65 years) or comorbidities. Patients were randomly assigned (1:1) using randomly permuted blocks (block size 4) by an interactive web response system to receive 28-day cycles of intravenous daratumumab (16 mg/kg, once per week during cycles 1–2, once every 2 weeks in cycles 3–6, and once every 4 weeks thereafter) plus oral lenalidomide (25 mg on days 1–21 of each cycle) and oral dexamethasone (40 mg on days 1, 8, 15, and 22 of each cycle; daratumumab group) or lenalidomide and dexamethasone alone (control group). Randomisation was stratified by International Staging System disease stage, geographical region, and age. Neither patients nor investigators were masked to treatment assignment. The primary endpoint was progression-free survival, which was centrally assessed, and a secondary endpoint was overall survival (both assessed in the intention-to-treat population). The safety population included patients who received at least one dose of the study treatment. The results presented here are from a prespecified interim analysis for overall survival, for which the prespecified stopping boundary was p=0·0414. This trial is registered with ClinicalTrials.gov, NCT02252172 . Findings: Between March 18, 2015, and Jan 15, 2017, 952 patients were assessed for eligibility, of whom 737 patients were enrolled and randomly assigned to the daratumumab group (n=368) or the control group (n=369). At a median follow-up of 56·2 months (IQR 52·7–59·9), median progression-free survival was not reached (95% CI 54·8–not reached) in the daratumumab group versus 34·4 months (29·6–39·2) in the control group (hazard ratio [HR] 0·53 [95% CI 0·43–0·66]; p<0·0001). Median overall survival was not reached in either group (daratumumab group, 95% CI not reached–not reached; control group, 95% CI 55·7–not reached; HR 0·68 [95% CI 0·53–0·86]; p=0·0013). The most common (>15%) grade 3 or higher treatment-emergent adverse events were neutropenia (197 [54%] patients in the daratumumab group vs 135 [37%] patients in the control group), pneumonia (70 [19%] vs 39 [11%]), anaemia (61 [17%] vs 79 [22%]), and lymphopenia (60 [16%] vs 41 [11%]). Serious adverse events occurred in 281 (77%) patients in the daratumumab group and 257 (70%) patients in the control group. Treatment-related deaths occurred in 13 (4%) patients in the daratumumab group and ten (3%) patients in the control group. Interpretation: Daratumumab plus lenalidomide and dexamethasone increased overall survival and progression-free survival in patients ineligible for stem-cell transplantation with newly diagnosed multiple myeloma. There were no new safety concerns. Our results support the frontline use of daratumumab plus lenalidomide and dexamethasone for patients with multiple myeloma who are ineligible for transplantation. Funding: Janssen Research & Development.